2021
DOI: 10.1101/2021.11.17.468992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of clathrin in exocytosis and the mutual regulation of endo- and exocytosis in plant cells

Abstract: Within the plant endomembrane system, the vesicle coat protein clathrin localizes to the plasma membrane (PM) and the trans-Golgi Network/Early Endosome (TGN/EE). While the role of clathrin as a major component of endocytosis at the PM is well established, its function at TGN/EE, possibly in exocytosis or the vacuolar pathway, is a matter of debate. This shared function of clathrin also opens a question whether plant cells possess a homeostatic mechanisms that balance rates of opposite trafficking routes, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Overall, in the course of experiments presented in this study, the localization of GN to the PM was most reliably observed with TIRF microscopy, rather than by CLSM; as discussed above, somewhat analogically, CCPs are always observed at the PM with TIRF microscopy, but the detection of fluorescent protein fusions of CLC at the PMs of RAM epidermis by CLSM is variable (e.g. Adamowski et al, 2018 , Adamowski et al, 2021b ).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Overall, in the course of experiments presented in this study, the localization of GN to the PM was most reliably observed with TIRF microscopy, rather than by CLSM; as discussed above, somewhat analogically, CCPs are always observed at the PM with TIRF microscopy, but the detection of fluorescent protein fusions of CLC at the PMs of RAM epidermis by CLSM is variable (e.g. Adamowski et al, 2018 , Adamowski et al, 2021b ).…”
Section: Resultsmentioning
confidence: 52%
“…We note that the detection of CLC markers by CLSM at the PMs of RAM epidermis is similarly limited (e.g. Adamowski et al, 2018 , Adamowski et al, 2021b ) despite CME being a housekeeping process.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, P34 might be a regulator of multiple clathrin-mediated vesicle trafficking pathways in Arabidopsis. Although debatable, some evidence exists that the activities of clathrin-dependent post-Golgi trafficking and CME are highly coordinated in plant cells 50, 63 . Recently, the recruitment of several endocytic components to the PM, including CLC1, CHC1, AP2M, AP2S, TPLATE and TML, was shown to be reduced in the ap1m2 mutant, but their protein levels to remain unchanged 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Different views co-exist in the literatures concerning what is (or are) the secretory domain(s) of TGN. For example, the clathrin domain was defined as the secretory domain (Adamowski et al, 2021;Shimizu et al, 2021), while other studies suggested uncoated vesicles as part of the secretion process. The TGN protein ECHIDNA is sitting on uncoated vesicles (Boutte et al, 2013) and is clearly involved in secretion of auxin carriers and cell wall components while playing no role in endocytosis or endocytic recycling (Gendre et al, 2011(Gendre et al, , 2013.…”
Section: Plant Tgn/ee: a Sorting Station For Proteins And Lipidsmentioning
confidence: 99%